A Recovery-Oriented Alternative to Hospital Emergency Departments for Persons in Emotional Distress: "The Living Room". (1st January 2014) - Shattell, Mona M.; Harris, Barbara; Beavers, Josephine; Tomlinson, Stella Karen; Prasek, Lauren; Geevarghese, Suja; Emery, Courtney L.; Heyland, Michelle
<x xml:space="preserve">Abstract</x> Persons with severe mental illness experience episodic crises, resulting in frequent visits to hospital emergency departments (EDs). EDs, however, are not the most effective treatment environments for these individuals who might better be served elsewhere in an environment based on recovery-oriented framework. The purpose of this study is to describe the lived experience of guests (persons in emotional distress) and staff (counselors, psychiatric nurses, and peer counselors) of a community, recovery-oriented, alternative crisis intervention environment—The Living Room (TLR). The total sample is comprised of 18 participants. An existential phenomenological approach was used for this qualitative, descriptive, study. Through non-directive in-depth interviews, participants were asked to describe what stands out to them about The Living Room. Interviews were audio-recorded, transcribed verbatim, and systematically analyzed using descriptive phenomenological methods of analysis by an interdisciplinary and community-based participatory research team. Participants' experiences in hospital EDs and inpatient psychiatric units contextualized the phenomenological experience of TLR environment. The final thematic structure of the experience of TLR included the following predominant themes: A Safe Harbor, At Home with Uncomfortable Feelings, and It's a Helping, No Judging Zone. Findings from this qualitative study of a recovery-based alternative to hospital EDs for persons in emotional distress are supported by anecdotal and empirical evidence that suggests that non-clinical care settings are perceived as helpful and positive.